2021
DOI: 10.1371/journal.pone.0245458
|View full text |Cite|
|
Sign up to set email alerts
|

Anemia in tuberculosis cases: A biomarker of severity?

Abstract: Introduction Anemia is a common condition at tuberculosis diagnosis, and there is evidence that its prevalence is higher in patients with tuberculosis than in those infected with Mycobacterium tuberculosis and healthy controls. Information about anemia during tuberculosis diagnosis is still scarce in the Brazilian population. The aim of this study was to describe the prevalence of anemia in patients with tuberculosis cared for at a referral center and its association with clinical forms of tuberculosis and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…43,44 Anaemia is associated with low CD4+ T-lymphocyte counts, delayed sputum culture conversion, and severe forms of TB. [45][46][47] Therefore, smoking, anaemia and undernutrition can be expected to synergistically increase the risk of unfavourable TB outcomes. While the optimal management of anaemia in DRTB is not known, barriers to integrating smoking cessation programs in DRTB care should be addressed.…”
Section: Dovepressmentioning
confidence: 99%
“…43,44 Anaemia is associated with low CD4+ T-lymphocyte counts, delayed sputum culture conversion, and severe forms of TB. [45][46][47] Therefore, smoking, anaemia and undernutrition can be expected to synergistically increase the risk of unfavourable TB outcomes. While the optimal management of anaemia in DRTB is not known, barriers to integrating smoking cessation programs in DRTB care should be addressed.…”
Section: Dovepressmentioning
confidence: 99%
“…Nutritional deficiencies such as iron, folate [ 12 , 13 ], vitamin B12 [ 14 ], and vitamin A [ 15 ] are the leading causes of anemia among under-five children in LMICs. Besides, diseases like malaria [ 16 ], Visceral Leishmaniasis (VL) [ 17 ], hookworm [ 18 ], schistosomiasis [ 19 ], cancer [ 20 ], tuberculosis [ 21 ], HIV/AIDS [ 22 ], and genetic hemoglobinopathies are commonly reported causes of anemia in developing and developed world [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Brazil on patients with TB suggests that anemia could be a biomarker of TB severity and that anemia was more frequent in the most severe clinical forms of this disease, such as meningeal and disseminated TB ( 52 ). The mitigation of iron deficiency and anemia in our study is likely due to the comparatively better inflammation-lowering effect (indicated by the reduced pro-inflammatory cytokines) in the FAD group.…”
Section: Discussionmentioning
confidence: 99%